An experimental study of fractionation of the rare earth elements in poplar plants (Populus eugenei) grown in a calcium-bearing smectite soil - Weber, Robert Joseph (Kansas State University, 2008)
Rare earth element (REE) concentrations were measured in a source (reference) clay Ca-smectite standard and in the roots, stems, and leaves of a species of poplar plant (Populus eugenei). The poplar plant was grown in the clay standard under controlled laboratory conditions during a period of about three months. REEs were shown to fractionate in the clay mineral and plant materials with greater fractionation observed in plant materials. The REE data provide insight into the process of weathering of clay minerals such as a Ca-bearing smectite and provide insight into the degradation of and the composition of clay minerals in the plant environment. The degradation process is not followed by significant interlayer ion exchange effect on remaining clay minerals in the root environment. REEs were found to be transported into complex forms, potentially as REE-carboxylic anion pair complexes. The plant materials in this study were in general heavy REE (HREE) enriched relative to the source clay minerals due to the complexation effect. The REE anomalies observed in this study, in addition to the Ce and Eu anomalies, may be explained by the selective uptake by the plant by an enzyme effect rather than due to the influence of oxidation-reduction. The enzyme influence was more evident in the REE distribution when compared among the plant organs. These REE characteristics described for the plants may eventually be incorporated with data from numerous other studies and also used as a guide in the assessment of the contribution of plant materials to dissolved REE content in surface water and groundwater.
Keywords: Rare earth element; Fractionation; Poplar; Clay; Complexation; Enzyme; Biology, General (0306); Geochemistry (0996); Geology (0372)